(untitled) (Orinoquia, 2021)
Objective: To determine the seroprevalence of anti-SARS-CoV-2 immunoglobulins (Ig) type G (IgG) in domestic dogs and cats, and their epidemiological association with positive COVID-19 RTq-PCR cases in the communes of the city of Villavicencio, Colombia. Methodology: An observational, analytical and cross-sectional study was carried out, in which antiSARS-CoV-2 IgG was measured in blood serum by indirect ELISA in a representative and random sample (n = 435) of felines (135) and canines (300) domestic in Villavicencio (N = 68,651). The Odds Ratio (OR) (p <0.05) was used to establish the risk factors associated with communes, age, species and COVID-19 positive owners, and Spearman’s Correlation (p <0.05) to identify the relation of positive cases SARS-CoV-2 RTq-PCR of humans in November 2020, compared to those found seroepidemiologically in pets, dogs and domestic cats of the 8 communes that make up the city of Villavicencio, during June to July of this year. Results: a general seroprevalence for IgG anti-SARS-CoV-2 of 4.6% (95% CI 3-7%) was found, specifically in canines of 3.67% and in felines of 6.67%; in turn, by communes 1st to 8th of: 0%, 13.63%, 6.67%, 8.06%, 1.02%, 4.76%, 4.82% and 2.5% respectively. By means of the Odds Ratio (OR), a risk association of 5.84% (95% CI 1.1-30.88) was evidenced in commune 2. A Spearman correlation of 0.32 was found, which is classified as weak positive correlation. Conclusion: 20 of 435 animals were seropositive for SARSCoV-2, 2 felines with a positive result expressed clinical signs such as cough, fever and decay. In this study, COVID-19 cases in humans have a low correlation with possible exposures to SARS-CoV-2 in dogs and cats in the city of Villavicencio. Our research on SARS-CoV-2 in companion animals is the first to be carried out in Latin America and aims to be a starting point to contribute to the epidemiology of the virus and contribute to public health in Colombia and the world.